Planejamento, implantação e gestão de um curso a distância a partir da percepção dos enfermeiros da atenção básica sobre a integralidade na saúde - Lemos, Suyane de Souza [UNESP] (2014)
Comprehensiveness in health is one of the pillars in the Brazilian public health system SUS and comes with a plurality of concepts that needs to be reflected as a way to strengthen health practice. The study aimed to discover the perception of primary care nurses and plan, implement and manage a distance learning course on comprehensiveness in health for nurses in primary care. The questions that guided the research were: How do primary care nurses perceive comprehensiveness in health? How can a distance learning course be planned, implemented and managed based on the study findings. To study the subjects' perception, the qualitative approach of phenomenology was chosen. Theoretical saturation was reached after the analysis of 22 interviews, with primary care nurses serving as the subjects. Interviews conducted by the researcher were audio-recorded, transcribed. After the transcripts, reports were analyzed individually, resulting in the themes: professional experience, the nurse's role in comprehensive care, the role of primary care, dimensions of comprehensive care, challenges for comprehensive care, strengths of comprehensive care. The themes unveiled that comprehensive health care is perceive since the professional education phase. The nurse's perspective on the role of primary care is focused on comprehensive health care and on the integration of health services. Only five of the subjects interviewed indicated the dimensions of comprehensive care, pointing towards the need to deepen knowledge on this aspect. Challenging elements emerged from the subjects, such as the biomedical centered model, lack of infrastructure, high demand, communication difficulties among the services to put comprehensive care in practice. On the other hand, the study subjects also strongly expressed the strengths as the Family health strategy itself, the matrix support of the Family Health Support Center in care production, the valuation of ...